Agroindustrialization through institutional innovation: transactions costs, cooperatives and milk-market development in the Ethiopian highlands - Holloway, Garth; Nicholson, Charles F.; Delgado, Christopher L.; Staal, Steven; Ehui, Simeon (International Food Policy Research Institute, 1999)
Some small-holders are able to generate reliable and substantial income flows through small-scale dairy production for the local market; for others, a set of unique transactions costs hinders participation. Cooperative selling institutions are potential catalysts for mitigating these costs, stimulating entry into the market, and precipitating growth in rural communities. Trends in cooperative organization in East-African dairy are evaluated. Empirical work focuses on alternative techniques for effecting participation among a representative sample of peri-urban milk producers in the Ethiopian highlands. The techniques considered are a modern production practice (cross-bred cow use), a traditional production practice (indigenous-cow use), three intellectual-capital-forming variables (experience, education, extension), and the provision of infrastructure (as measured by time to transport milk to market). A Tobit analysis of marketable surplus generates precise estimates of non-participants’ ‘distances’ to market and their reservation levels of the covariates—measures of the inputs necessary to sustain and enhance the market. Policy implications focus on the availability of cross-bred stock and the level of market infrastructure, both of which have marked effects on participation, the velocity of transactions in the local community and, inevitably, the social returns to agroindustrialization.